EMBLEMATIC GENRE - de Souza Brandão, Antônio Jackson (2009)
In this article we will present the emblematic genre, creation of the Italian AndreaAlciati in 16th century (1531) that dominates the European society until the 18th, but disappearsin 19th century. We will also show the difficulty and the possibility of reading today, in21th century, texts, images and emblems of 17th century without having all the referential of thatmoment.